2016
DOI: 10.7448/ias.19.7.21105
|View full text |Cite
|
Sign up to set email alerts
|

The future of PrEP among transgender women: the critical role of gender affirmation in research and clinical practices

Abstract: IntroductionGlobally, transgender (“trans”) women are one of the key populations most disproportionately impacted by HIV. Pre-exposure prophylaxis (PrEP) is the newest and most promising biomedical HIV prevention intervention to date. This paper reviews relevant literature to describe the current state of the science and describes the potential role of PrEP among trans women, including a discussion of unique considerations for maximizing the impact of PrEP for this vulnerable population.MethodsAvailable inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 55 publications
6
133
1
2
Order By: Relevance
“…These findings also extend to ART for preexposure prophylaxis (PrEP) to prevent HIV acquisition, as TW may have concerns about possible DDIs between PrEP and feminizing HT. 20 In looking at the evidence for DDIs, published studies predominantly address HT-ART DDI between ART (typically NNRTI/PI-based regimens) and ethinyl estradiol, a synthetic estrogen used in contraception but not currently recommended for feminizing HT due to increased thrombotic risk. 21 A recent systematic review found that the most noteworthy interactions occurred for cisgender women using NNRTIs, and particularly efavirenz, although these outcomes were predominantly pharmacokinetic in nature and assessed interactions at doses used for contraception rather than feminizing HT.…”
Section: Braun Et Almentioning
confidence: 99%
“…These findings also extend to ART for preexposure prophylaxis (PrEP) to prevent HIV acquisition, as TW may have concerns about possible DDIs between PrEP and feminizing HT. 20 In looking at the evidence for DDIs, published studies predominantly address HT-ART DDI between ART (typically NNRTI/PI-based regimens) and ethinyl estradiol, a synthetic estrogen used in contraception but not currently recommended for feminizing HT due to increased thrombotic risk. 21 A recent systematic review found that the most noteworthy interactions occurred for cisgender women using NNRTIs, and particularly efavirenz, although these outcomes were predominantly pharmacokinetic in nature and assessed interactions at doses used for contraception rather than feminizing HT.…”
Section: Braun Et Almentioning
confidence: 99%
“…First, transgender women’s healthcare needs, HIV risk profile, and barriers to HIV prevention and treatment are distinct from gay and bisexual men (911). Therefore, transgender women are highly likely to have different challenges related to biomedical HIV prevention product use than these men, making extrapolation from gay and bisexual men-only studies inappropriate (7, 12–14). Second, to our knowledge, only one study that has examined gay and bisexual men and transgender women as one demographic has recruited a sufficient number of transgender women to power a separate, transgender-focused analysis (3, 4, 15, 16).…”
Section: Introductionmentioning
confidence: 99%
“…We examine the healthcare system and the labor market as two gendered institutions that influence BMSM’s preventive healthcare practices (Dovel et al, 2015; Fleming & Dworkin, 2016) and show how BMSM are negatively impacted by heteronormatively gendered institutional processes in health care and labor market settings. Assumptions about gender as a binary category mean that men often pay a penalty—in the form of social exclusion and stigma—for being gender non-conforming (Frye et al, 2015; Lerner & Robles, 2017; Messner, 1997; Sabo, 2005; Sevelius, Deutsch, & Grant, 2016). …”
Section: Introductionmentioning
confidence: 99%